Observational evidence for enhanced magnetic activity of superflare stars - Christoffer Karoff (Nature Portfolio, 2016)
Superflares are large explosive events on stellar surfaces, much larger than solar flares, but it remains unclear whether they share the same origin. Here, the authors analysed 48 superflare stars and determine the relation between their chromospheric activity and the occurrence of superflares.